VDBP, free 25-(OH)D levels and markers of psychophysical stress in professional football players - Zagrodna, A.; Ksiazek, A.; Slowinska-Lisowska, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: It has been proposed that serum free 25-hydroxyvitamin D (25-(OH)D) may better reflect vitamin D action than total 25-(OH)D based on the free hormone hypothesis. Vitamin D plays an active role in muscle inflammatory response, protein synthesis, and regulation of skeletal muscle function. Strenuous muscle contractions during exercise may induce mechanical muscle damage. Thus, monitoring of psychophysical stress markers in athletes may help to tailor training/competition and recovery regimes to optimize performance. Therefore, the aim of our study was to check the relationship between free 25-(OH)D levels and blood count, iron, ferritin, testosterone (T), cortisol (C), creatine kinase (CK), liver enzymes (ALT, AST) and high-sensitivity C-reactive protein (hs-CRP) in professional football players.